2022
DOI: 10.1002/er.7969
|View full text |Cite
|
Sign up to set email alerts
|

Development of amorphous Fe‐doped nickel‐cobalt phosphate (FexNiCo(PO4)2) nanostructure for enhanced performance of solid‐state asymmetric supercapacitors

Abstract: Summary Tremendous efforts have been made to create significant energy storage devices using nanoscale design and hybrid techniques. Toward this end, herein, we have fabricated, a binder‐free, amorphous iron‐doped nickel‐cobalt phosphate (FexNiCo(PO4)2, ie, F‐NCP) thin film on stainless steel substrate using a facile successive ionic layer adsorption and reaction (SILAR) method. Furthermore, the influence of Fe doping concentration on physico‐chemical properties is investigated. The various F‐NCP‐series electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Conversely, in a different scenario where b is set to 0.5, the charge storage mechanism is influenced by the diffusion-controlled current (battery type). 37 Figure S6a−c displays the logarithmic relationship between current density and scan rate for CoNiO 2 , MoS 2 , and the MoS 2 /CoNiO 2 hybrid structure samples. The calculated "b" values for these samples are 0.55, 0.51, and 0.56, respectively.…”
Section: Half-cell Measurementmentioning
confidence: 99%
“…Conversely, in a different scenario where b is set to 0.5, the charge storage mechanism is influenced by the diffusion-controlled current (battery type). 37 Figure S6a−c displays the logarithmic relationship between current density and scan rate for CoNiO 2 , MoS 2 , and the MoS 2 /CoNiO 2 hybrid structure samples. The calculated "b" values for these samples are 0.55, 0.51, and 0.56, respectively.…”
Section: Half-cell Measurementmentioning
confidence: 99%
“…Reports issued on tri/multimetallic phosphates based on nickel and cobalt phosphate are tabulated in Table 4. 59,61,115,124–127…”
Section: Nickel/cobalt-based Phosphate Materials For Hybrid Supercapa...mentioning
confidence: 99%
“…For example, Co, Ni, and Fe have similar atomic structures, which helps improve electrochemical activity and retain surface morphology. Although only one report is available on Fe-doped Ni–Co phosphate electrode material, 124 it was found that adding Fe ions resulted in multiple oxidation states and excellent conductivity. 128,129 A solid-state device was fabricated by combining Fe-doped Ni–Co phosphate as cathode and rGO as anode.…”
Section: Nickel/cobalt-based Phosphate Materials For Hybrid Supercapa...mentioning
confidence: 99%
“…In recent decades, Transition metal phosphates have been widely studied as cathode materials for supercapacitors (SCs) and secondary rechargeable batteries due to their excellent electrical conductivity, active electrochemical properties, and good stability. [19][20][21][22][23][24] Besides, it is widely known that the synergistic effect of Ni and Co species plays a critical role in the remarkable electrochemical performance of NiÀ Co binary compounds. [25,26] Zhang et al synthesized nanoflowers-like NH 4 (Ni,Co)PO 4 on carbon fibers via a hydrothermal method.…”
Section: Introductionmentioning
confidence: 99%